Aerobic interval training in patients with heart failure and an implantable cardioverter defibrillator: a controlled study evaluating feasibility and effect. (29th August 2020) - Isaksen, Kjetil; Munk, Peter S; Valborgland, Torstein; Larsen, Alf I
Abstract: Background: Aerobic interval training (AIT) has been shown to be superior to moderate continuous exercise training in improving exercise capacity and endothelial function in patients with both coronary artery disease and heart failure (HF). The objective of this study was to evaluate this training modality in patients with HF and an implantable cardioverter defibrillator (ICD) with regard to feasibility, safety, and effect. Methods: We prospectively included 38 patients with an ICD: 26 patients participated in an AIT programme for 3 months, while 12 patients served as controls. At baseline and 12-week follow up, patients were assessed with a maximal ergospirometry stress test, echocardiography, endothelial function testing, and ICD interrogation. Results: No exercise-related adverse events occurred during or soon after the training sessions. ICD interrogation revealed no sustained arrhythmias, antitachycardia pacing, or ICD discharge related to exercise sessions. The AIT programme led to a significant increase in peak oxygen uptake, cycle ergometer workload, and endothelial function compared to the control group. The training programme was safe and not associated with any adverse events or ICD-related complications. Conclusions: An AIT programme is feasible and seems safe in a well-treated, stable ICD population. Further, AIT for 3 months results in significantly increased aerobic capacity and endothelial function in this population.